Narcolepsy with cataplexy in patients aged over 60 years: a case-control study - Kovalská, Petra; Kemlink, David; Nevšímalová, Soňa; Maurovich Horvat, Eszter; Jarolímová, Eva; Topinková, Eva; Šonka, Karel (Sleep medicine, 2016)
OBJECTIVE: Narcolepsy with cataplexy (NC) is a chronic disabling disease; however, there are insufficient data on older NC subjects. METHODS: A cross-sectional evaluation on health and social status, including intensity and progression of NC symptoms, was performed on 42 NC patients (age 71.9 years ± 7.5) and 46 age-and-sex-matched controls (age 72.2 years ± 7.0). RESULTS: A greater proportion of patients than controls suffered from hypertension and type 2 diabetes. More controls had a history of treated depression; however, according to the Geriatric Depression Scale, more NC patients scored in the range of depression. There were no significant differences in Addenbrook Cognitive Examination scores. Average physical fitness assessed by the Short Physical Performance Battery was lower in the NC group. The frequency of meeting with family, friends, and participation in hobbies or sports did not differ between the two groups. CONCLUSIONS: Symptoms of NC were present throughout life. Comorbidities and lower physical fitness, which are known to be present in young and middle-aged NC subjects, were also present in older patients. Although NC subjects were less professionally active during their lifetime, they did not differ from controls in important social parameters in older age.
Keywords: Physical Fitness; senioři; Cross-Sectional Studies; Aging; deprese; Cataplexy; Statistics, Nonparametric; Male; komorbidita; Hypertension; Chronic Disease; Depression; chronická nemoc; Middle Aged; průzkumy a dotazníky; mužské pohlaví; Diabetes Mellitus, Type 2; studie případů a kontrol; tělesná výkonnost; průřezové studie; neparametrická statistika; diabetes mellitus 2. typu; Narcolepsy with cataplexy; věkové faktory; Quality of life; ženské pohlaví; Humans; Elderly; Comorbidity; Surveys and Questionnaires; Chi-Square Distribution; lidé středního věku; hypertenze; rozdělení chí kvadrát; Age Factors; kataplexie; Female; Aged; lidé; Case-Control Studies